Absence of colon as the predominant risk factor for liver fibrosis in adults requiring home parenteral nutrition. (February 2020) - Christensen, S.R.; Olesen, A.L.K.; Kristensen, L.H.; Jensen, M.H.; Rasmussen, H.H.; Køhler, M.; Schmidt, S.; Vinter-Jensen, L.; Holst, M.
Summary: Background: Liver fibrosis is a well-known complication of long-term use of parenteral nutrition in patients with intestinal failure associated to the nutrient composition in parenteral nutrition. This study investigates the prevalence of significant liver fibrosis and identifies risk factors for liver fibrosis. Methods: This was a retrospective study of 35 parenteral nutrition-dependent patients with intestinal failure and 54 patients with intestinal insufficiency and oral nutrition only with a valid liver stiffness measurement obtained with transient elastography from November 2016 to August 2018. Clinical and demographic parameters including age, fat mass index and fat-free mass index, intact colon or colectomy, and nutritional management were analyzed for their association with liver stiffness. Results: A prevalence for liver fibrosis (liver stiffness >7.0 kPa) was established at 37.1% in parenteral nutrition-dependent patients and at 22.2% in patients on oral nutrition. Several factors were significantly and independently associated with liver fibrosis including lipids in home parenteral nutrition (OR 10.66, p = 0.010) and colectomies (OR 3.24, p = 0.036). Conclusion: More than a third of patients receiving home parenteral nutrition have liver fibrosis. Several risk factors were demonstrated such as the amount of lipids and performed colectomies despite current international guidelines for lipids are followed. Our findings emphasize suggest a new perspective to prevent significant hepatic complications: colectomies.